2020
DOI: 10.3390/jcm9082437
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bispectral Index Monitoring Does Not Change Intraoperative Exposure to Volatile Anesthetics in Children

Abstract: The exposure of infants and children to volatile anesthetics, such as sevoflurane, has been a topic of concern with respect to the potential risk for long term neurocognitive effects. The primary objective of this study was to determine whether the perioperative utilization of Bispectral Index (BIS) monitoring alters the sevoflurane delivery and exposure to children. This is a prospective randomized trial of two groups of healthy ambulatory day surgery patients (2 to 12 years). The patients in both groups had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
(46 reference statements)
1
9
1
Order By: Relevance
“…Sullivan’s trial found that in 54 children aged 2–12 undergoing orthopedic surgery, the BIS-monitoring group (maintaining BIS values of 40–60) reduced sevoflurane exposure compared with the normal group, but the difference was not statistically significant [ 49 ]. In our trial, however, the intraoperative EtSevo was significantly reduced in the E group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sullivan’s trial found that in 54 children aged 2–12 undergoing orthopedic surgery, the BIS-monitoring group (maintaining BIS values of 40–60) reduced sevoflurane exposure compared with the normal group, but the difference was not statistically significant [ 49 ]. In our trial, however, the intraoperative EtSevo was significantly reduced in the E group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study reported that BIS monitoring for the guidance of propofol–remifentanil anesthesia did not result in a reduced consumption of remifentanil [ 51 ]. Some researchers also found that using BIS monitoring did not influence the extubation time and discharge time [ 49 , 52 ]. Our results were similar to those in the above reports; the remifentanil infusion rate and MAP in the anesthesia maintenance period were similar between the two groups, and extubation time and discharge time also showed no differences between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sum of these values results in the numerical values called Spectral Entropy. The first algorithm ever to be used in the clinical practice has been defined and applied in the M-Entropy modules S/5 (GE Healthcare, Helsinki, Finland) [ 10 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The EEG data are collected through an adhesive sensor made of three electrodes applied on the fronto-temporal region.…”
Section: Multimodal Monitoring Techniques For the Degree Of Hypnosmentioning
confidence: 99%
“…The usage of monitoring techniques for the degree of hypnosis in the case of pediatric patients is limited and is not validated. Numerous studies have analyzed the statistical correlations between BIS and Entropy for different age groups but have not identified strong statistical correlations between BIS/Entropy values and anesthetic drugs concentrations in infants vs. pediatric patients (aged over 1 year old) [ 42 ]. Davidson et al carried out a study regarding the performance of BIS and Entropy for different age groups in pediatric patients.…”
Section: Multimodal Monitoring Techniques For the Degree Of Hypnosmentioning
confidence: 99%